Evaluation and comparison of different calcified structures for the ageing of cyprinid fish leuciscus vorax (heckel, 1843) from karakaya dam lake, Turkey - Rashid, Rzgar Farooq; Basusta, Nuri (Parlar Scientific Publications, 2021)
The aim of the present study was the comparative analysis of accuracy, precision, and quality control in age determination for Leuciscus vorax (Heckel, 1843) using different calcified structures: dorsal fin, operculum, otoliths, scales, and vertebrae. Specimens were collected monthly from the Karakaya Dam Lake, Malatya, Turkey using gillnets from September 2016 through March 2017. A total of 46 female fish (ranged 38.7-69.5 cm of total length) and 27 male fish (ranged 41.1-58.8 cm of total length) were measured collecting the calcified structures considered. The standard procedures for recovering, preparing, and reading of the aforementioned calcified structures for the age determination were followed. The precision of readers and structures were estimated, and the ageing error was determined by coefficient of variation (CV, %), average percentage error (APE, %), and percentage of agreement (PA, %). The highest PA (63.0%) with lowest APE (3.3%) and CV (4.7%) were recorded for vertebrae, while the lowest PA (32.9%) and highest APE (8.1%) and CV (11.4%) were determined for dorsal fins. Age estimates of vertebrae were compared with other ageing structures; the highest PA (31.5%) and lowest APE (3.6%) and CV (5.0%) were found between operculum and vertebrae. It was observed that the otolith of L. vorax was covered by a dark opaque, reducing the clarity of growth lines under the microscopic. Hence, the age determination of L. vorax from its otolith might not provide a reliable age estimate. In sum, vertebrae was the most reliable structure for the age estimate of L. vorax followed by operculum, scale and dorsal fin. © 2021 Parlar Scientific Publications. All rights reserved.
Keywords: Age determination; Aspius vorax; Dorsal fin; Operculum; Scales; Vertebrae